Between power and the word: the speeches of the San Martin square - de la Cruz, Kevin (2023)
This study aims to describe and analyze the reproduction of power relations in the political discourse of the speakers of the San Martin square during the period 2021. For the analysis of the study, the case study of the Rímac Llaqta association has been applied and from it, speeches pronounced by its main speakers extracted from audiovisual sources have been selected. Interviews were also conducted with the speakers themselves. Taking into consideration the bibliographic review and the analysis of the speeches, as well as the qualitative and interpretative nature of the study, the research argues that the power relations -which emerge from the speeches- are relations whose level of effectiveness is uncertain, since they are subject to improvisation, both in their formation and in their exposition, which may determine an effective resistance to the power that such speeches could create. The research concludes that the reproduction of power relations in Rimac Llaqta’s political discourses is based on the legitimacy and dominance of the social fighter in ideological knowledge and on the existence of visible and invisible objectives that have in common the capture of political power.